The synthesis of 4-amino-5-(quinolin-2-yl)-4H-1,2,4-triazole-3-thiol and its interaction with aldehydes - D. М. Zozulynets; A. G. Kaplaushenko; A. S. Korzhova (Журнал органічної та фармацевтичної хімії, 2021)
Aim. To synthesize 4-amino-5-(quinolin-2-yl)-4H-1,2,4-triazole-3-thiol and study its reactivity in the reaction with aldehydes. Results and discussion. 4-Amino-5-(quinolin-2-yl)-4H-1,2,4-triazole-3-thiol was synthesized, and a number of 4-(ethyl, aryl)idenamino derivatives were obtained on its basis. Experimental part. Using a series of four successive reactions based on quinoline-2-carboxylic acid, 4-amino-5-(quinolin-2-yl)-4H-1,2,4-triazole-3-thiol was synthesized; its interaction with aldehydes allowed to obtain a number of 4-(ethyl, aryl)idenamino derivatives. The structure of all compounds synthesized was confrmed by IR and 1H NMR spectroscopy, as well as by elemental analysis, and their purity by thin layer chromatography. Conclusions. 4-Amino-5-(quinolin-2-yl)-4H-1,2,4-triazole-3-thiol has been synthesized. It has been found that its interaction with aldehydes leads to the formation of new 4-((ethyl, aryl)idenamino)-5-(quinolin-2-yl)-4H-1,2,4-triazole-3-thiols.